THE ROLE OF WOMEN IN THE SOCIETY AND CHURCH DEVELOPMENT - ONYENZE CHINYERE R; EBEBE I. E. (International Studies Journal)
Women from the early days of the Church have contributed immensely to the development of the society and Church. The need to recognize the contributions of the women to socio-religious and economic spheres of our national life is becoming increasingly urgent, especially now, that Nigeria is in dire need of rapid socio-cultural cum economic development. The work, which is anchored on preference theory, will explore the concepts of the Holy books about women, concepts of African culture and about women; subordination of women, total neglect of women from advent of Christianity in Nigeria; women in Church history, the role of women in the development of society; women in Church Development; factors affecting the role of women in the society and church development and then conclusion. The paper recommends among others that women should always recognize their worth and position in the quest for societal development and national transformation and so should brace up to confront gallantly all the social, religious, economic and political impediments that hold then down.